2015
DOI: 10.1186/s12955-015-0345-y
|View full text |Cite
|
Sign up to set email alerts
|

An in-depth psychometric analysis of the Connor-Davidson Resilience Scale: calibration with Rasch-Andrich model

Abstract: BackgroundThe Connor-Davidson Resilience Scale (CD-RISC) is inarguably one of the best-known instruments in the field of resilience assessment. However, the criteria for the psychometric quality of the instrument were based only on classical test theory.MethodThe aim of this paper has focused on the calibration of the CD-RISC with a nonclinical sample of 444 adults using the Rasch-Andrich Rating Scale Model, in order to clarify its structure and analyze its psychometric properties at the level of item.ResultsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
56
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 42 publications
(53 reference statements)
10
56
0
3
Order By: Relevance
“…Factor analysis of the CD-RISC scores revealed two significant factors reflecting ‘Adaptability’ and ‘Self-efficacy’, these were similar to other factor analyses of the same resilience inventory ( Arias Gonzalez et al, 2015 ; Campbell-Sills and Stein, 2007 ; Green et al, 2014 ). Of the two factors, we observed that the ‘self-efficacy’ factor was significantly associated with DNAm age acceleration in the PTSD group (r = 035).…”
Section: Discussionsupporting
confidence: 77%
“…Factor analysis of the CD-RISC scores revealed two significant factors reflecting ‘Adaptability’ and ‘Self-efficacy’, these were similar to other factor analyses of the same resilience inventory ( Arias Gonzalez et al, 2015 ; Campbell-Sills and Stein, 2007 ; Green et al, 2014 ). Of the two factors, we observed that the ‘self-efficacy’ factor was significantly associated with DNAm age acceleration in the PTSD group (r = 035).…”
Section: Discussionsupporting
confidence: 77%
“…For these reasons, the results of the present study differ from the five dimensions in results of a study by Connor & Davidson (2003) or four, three or two dimensions in results of studies by Crespo et al (2014), Serrano-Parra et al (2012 and Green et al (2014), respectively. However, in our opinion, these sub-dimensions are only different aspects within a one-dimensional operational definition of the construct of resilience according to results of studies by Arias-González et al (2015), Ponce-Cisternas (2015) and others.…”
Section: Discussionmentioning
confidence: 97%
“…Second, the use of the Kaiser-Guttmann criterion alone to decide how many factors to retain was a poor choice because it can easily lead to overfactoring [ 22 ]. Finally, the names of the first three factors could be confusing because they combined dissimilar concepts [ 23 ].…”
Section: Introductionmentioning
confidence: 99%